COVID-19 in Gastroenterology Departments: The Impact of the First Wave - Leal,Tiago (2021)
Abstract: Introduction: Coronavirus disease 2019 (COVID-19) is a global pandemic that has severely affected health care systems around the world. During the emergency state declared in Portugal in the months of March and April 2020, there was a severe reduction in medical activity in order to reduce the pressure on health systems. This study aimed to assess the impact of COVID-19 in gastroenterology departments across Portugal and the strategies developed to overcome this challenge. Methods: This was a cross-sectional study based on an online survey. A detailed questionnaire concerning different aspects of gastroenterology department activity was sent via e-mail to the heads of gastroenterology departments of Portuguese District Hospitals (Núcleo de Gastroenterologia dos Hospitais Distritais). Two periods were assessed, i.e., the emergency state and the recovery period between May and September. The responses were collected between September and October 2020. Results: A total of 21 hospitals were enrolled (80.8% response rate). Twenty-eight percent of the responders reported healthcare professionals from their unit infected with COVID-19. At least 1 member (mostly fellows) of the department was deployed to another workplace in 66.7% of the hospitals. During the emergency state, 47.6% of the hospitals only performed urgent/emergent endoscopic procedures. In 38.5% of the hospitals the need to ration personal protective equipment led to the suspension of endoscopic training. Regarding the recovery period, nonurgent procedures were restarted in almost all of the centers. The same was reported for the colorectal cancer screening program. Remarkably, 81% of the responders confirmed that they had postponed procedures at patients’ request for “fear of getting infected.” Remote consultation was maintained in 81% of the hospitals. Globally, the fellows had resumed their training. Discussion/Conclusion: This study provides a snapshot of the impact and consequences of the first wave of the COVID-19 pandemic across Portuguese hospitals. It is important to understand how the gastroenterology world dealt with the first impact of COVID-19 and what strategies were implemented in order to better prepare for what might follow.